Understanding feminist issues by reading Daniyal Mueenuddin’s “In Other Rooms, Other Wonders” in a prose class - Sri Sumaryani; Maria Johana Ari Widayanti; Ruly Indra Darmawan (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
The teaching of English literary works in a foreign language context remains a textual-oriented activity. Students were required to comprehend the linguistic and thematic features of the texts. However, more often than not, students were not aware of the real sociocultural, economic, and political conditions from which the text was based because they focused more on understanding the textual contents of the text. In Indonesia where English was still considered as a foreign language, the phenomenon was common. This paper examined the results of a contextual approach given to students when discussing a literary text. The contextual approach was implemented in three stages: pre-reading activities; reading, discussing, and analyzing the text by paying attention to its linguistic features and plot; and connecting the text with real-life situations. The study involved 31 English Literature students at Universitas Negeri Semarang from the third semester. The text discussed was a short story titled “In Other Rooms, Other Wonders” which contained feminist issues. The researchers also used questionnaires and observed the students’ activities during the three stages to enrich the data. The results revealed that the approach helped the students to understand feminist issues more comprehensively. They were able to relate the circumstances depicted in the story with the real sociocultural, economic, and political conditions of the society where the story was based. The results also suggested that the method was effective in developing the students’ literacy skills.